Evaluación, de instilación de dos anestésicos locales, mas dexmedetomidina, intraperitoneal, como coadyuvante en analgesia multimodal, en ovariohisterectomía, clinica veterinaria snap Ambato - Bonilla Silva, Julio Andrés (2024)
Ovariohysterectomy is one of the most frequent surgical procedures in the routine clinic of pets, which is considered a painful procedure that in some cases is not controlled, where the manipulation and resection of organs and tissues is involved, therefore, the objective of the present experimentation is; to evaluate the instillation of 2 local anesthetics, plus dexmedetomidine, intraperitoneal, as coadjuvant in multimodal analgesia, in ovariohysterectomy. For this purpose, four treatments were established, comprised by: T0 (control), T1 (control), T2 (control) and T3 (control): T0 (control), T1: intraperitoneal lidocaine, T2: intraperitoneal bupivacaine, T3: lidocaine plus intraperitoneal bupivacaine and T4: lidocaine plus intraperitoneal dexmedetomidine, evaluating their pharmacological influence on heart rate (Fc), respiratory rate (Fr), oxygen saturation (SpO2), mean arterial pressure (MAP), capnography (EtCO2), body temperature (T°), Glasgow pain scale recording at 30 minutes, 8 hours and 24 hours after OVH, and additionally an economic analysis. The results showed that during surgery 50% of the patients in the T0 group and 12.5% in the T1 group experienced pain, while 100% of the animals in the T2, T3 and T4 groups did not experience any painful sensation based on the intraoperative recordings of physiological constants. In addition, significant statistical differences (P<0. 05) on pain scores by application of the Glasgow scale at 30 minutes, 8 hours and 24 hours after OVH, observing that T1 (lidocaine) patients exhibited an analgesic plane at 30 minutes post-surgery compensated, however, the other study groups received a score > 6 points in that evaluation period, considering that, at 8 hours post-surgery, the patients who received local anesthetics instilled in the peritoneum did not require analgesic rescue, since the score of the scale under study was scored below 6 points, finally when performing said recording at 24 hours after surgery, it was observed that all patients maintained adequate analgesia. We conclude that intraperitoneal instillation of local anesthetics provides a compensated post-surgical analgesic plane.